Microarray technology - Zvara, Ágnes; Kitajka, Klára; Faragó, Nóra; Puskás, László G (Acta Biologica Szegediensis, 2015)
The normal functions of the cells are based on a strict and regulated expression of various genes. If this precise hierarchy of gene actions becomes unregulated or disturbed due to different genetic or environmental effects, the result will be abnormal cellular function that eventually could lead pathological alterations, including carcinogenic transformation or apoptosis. To understand the complex mechanisms and networks involved in biological processes and diseases, it is not enough to analyze isolated pathways, single gene functions or a single genetic event. A living organism has to be studied as a complex system and all genes involved in different biological processes need to be analyzed simultaneously: a systems biology approach should be applied. In the beginning of the 1990’s years, a new, high throughput technology - called microarray technology – was developed to measure the expression levels of large numbers of genes simultaneously or to genotype multiple regions of a genome. Microarrays have dramatically accelerated many types of investigation since a microarray experiment can accomplish many genetic tests in parallel. This review summarizes some of aspects of the microarray technology, including sample preparations, application possibilities and data analysis.